Good or bad visits? An interpretative phenomenological analysis of the experience of supervised college teachers in Central China - Wenting Gong; Chuang Xu; Jian-Hong Ye (Humanities & Social Sciences Communications)
Abstract Instructional supervision, an internal, dynamic system for monitoring and evaluating teaching quality in Chinese colleges, positively impacts teaching quality assurance and enhancement. While prior studies have theoretically explored instructional supervision, few have examined how supervised college teachers perceive, interpret, and respond to supervision experiences and how their noticing shifts under supervised circumstances. Using interpretative phenomenological analysis (IPA), this study explored the supervised experiences of eight Chinese college teachers in Central China through written narratives and semi-structured interviews. Three core themes emerged: supervisors’ existence, teachers’ emotions, and students’ performance, and six sub-themes related to supervisors, teachers and students were also identified: the symbolic person and the embodied actions, the sudden nervousness and the gradual relaxation, the unexpected cooperation and the closer teacher-student rapport. These interconnected themes form a dynamic chain of progressive noticing, and indicating that instructional supervision acts as a catalyst for teacher noticing shifts, a spark for teachers’ emotional labor, and a facilitator of teacher-student rapport. This study not only broadens the scope of instructional supervision but also offers new insights into enhancing college teachers’ professional development and teaching effectiveness within similar higher education institutions.